Anemia among Pediatric Critical Care Survivors: Prevalence and Resolution. (27th February 2013) - Ngo, Quang N.; Matsui, Doreen M.; Singh, Ram N.; Zelcer, Shayna; Kornecki, Alik
Abstract : To determine the incidence of anemia among pediatric critical care survivors and to determine whether it resolves within 6 months of discharge. Design . A prospective observational study. Patients with anemia upon discharge from the pediatric critical care unit (PCCU) underwent in hospital and post hospital discharge followup (4–6 months) for hemoglobin (Hb) levels. Setting . A medical-surgical PCCU in a tertiary care center. Patients . Patients aged 28 days to 18 years who were treated in the PCCU for over 24 hours. Measurements and Main Results . 94 (24%) out of 392 eligible patients were anemic at time of discharge. Patients with anemia were older, median 8.0 yrs [(IQR 1.0–14.4) versus 3.2 yrs (IQR 0.65–9.9) (P < 0.001 )], and had higher PeLOD [median 11 (IQR 10–12) versus 1.5 (1–4) (P < 0.001 )], and PRISM [median 5 (IQR 2–11) versus 3 (IQR 0–6) (P < 0.001 )] scores. The Hb level normalized in 32% of patients before discharge from hospital. Of the 28 patients who completed followup, all had normalization of their Hb in the absence of medical intervention. Conclusions . Anemia is not common among patients discharged from the PCCU and recovers spontaneously within 4–6 months.